CEMENT SUB SECTOR STOCK RETURNS BASED ON ECONOMIC VALUE ADDED AND MARKET VALUE ADDED - Kustina, Lisa; Rakhmat, Adrianna Syariefur (STIE Kusuma Negara, 2019)
The main goal of a company is not to make profit, but to cash. One of the main indicators in generating cash is to maximize the value of the company's shares as a form of giving satisfaction to the company's shareholders. In an effort to achieve this, the company will try to increase cash flow and profits to be obtained. This research is a quantitative and causal associative study that measures the effect of EVA and MVA on stock price returns using panel data regression analysis. The sample in this study is 4 (four) cement companies that have gone public with a time period of 9 (nine) years from 2010 to 2018. The results of this study indicate that the effect of EVA and MVA on stock returns is 11.7% while 88, The remaining 3% is influenced by other variables not mentioned in the model. Based on partial tests, EVA has a negative and not significant effect on stock returns. While MVA has a positive and not significant effect on stock returns.